Use of the Ready –to- Use Therapeutic Foods (RUTFs), for the Management of Malnutrition in People Living with HIV/AIDS in Omdurman Hospital (VCT Centre) - Yousif Abo, Dr. Suzan Ail; AwadSalih, Osama; Osman Hamed, Co.Mohamed (International Research in Medical and Health Sciences, 2019)
This study is an observational "before and after" randomized controlled trial study, using routinely collected data. The main objective is to evaluate the outcomes of patients with acquired immunodeficiency syndrome (AIDS) provided with Ready-to-use therapeutic food (RUTF) and nutritional counseling. A total of 7 HIV patients were selected from those who attending Omdurman VCT Center at Omdurman Teaching Hospital during the period from September 2008 to March 2009.. Primary data was collected directly from HIV patients who attended Omdurman VCT Center at Omdurman Teaching Hospital using a questionnaire in addition to a checklist to record weight changes during intake of food regimen (RUTF). The Statistical Package for Social Science (SPSS) version 12.0 was used for data analysis. Results showed that 71.4% of the respondents in the age group 31–40 years, 71.4% were males and 28.6% were females. Most of the respondents (57.1%) were married, having marginal occupations. The majority of the respondents (71.4%) used pre ARV drugs as major medication, of them, 42.9% used it for a period from 6 months to one year. The majority of the respondents (85.7%) did not complain about any type of food and drug interactions. The average Body Mass Index of the respondents (BMI) showed a relatively normal range (18–25). Use of RUTF showed improvement effect on patients, where T-test showed that there are significant differences in median weights between patients and the control group (P ≤ 0.05). The study highly recommends conduction of detailed studies on the importance of RUTF and other nutritional aspects for HIV/AIDS.